Towards a comparative framework of demographic resilience - Capdevila, P; Stott, I; Beger, M; Salguero-Gomez, R (Elsevier, 2020)
In the current global biodiversity crisis, developing tools to define, quantify, compare, and predict resilience is essential for understanding species' responses to global change. Disparate interpretations of resilience have, however, hampered the development of a common currency to quantify and compare resilience across natural systems. Most resilience frameworks focus on upper levels of biological organisation, especially ecosystems or communities, which adds complication to measuring resilience with empirical data. Surprisingly, a quantifiable definition of resilience does not exist at the demographic level. Here, we introduce a framework of demographic resilience that draws on existing concepts from community and population ecology, with an accompanying set of metrics that are comparable across species.